Gratitude, Family Support, and Meaningfulness of Life: An Analysis of Thesis Writing Students - Fathul Mu’in; Andry Rahman Arif; Intan Islamia; Fadli Hermawan (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
Abstract. The purpose of this research is to understand the correlation between gratitude and family support received, with the level of meaning in the lives of students who are in the process of completing their thesis. The population under investigation in this study consists of students who are finalizing their theses in the Faculty of Ushuluddin and Religious Studies at Raden Intan Lampung State Islamic University. The sampling method employed was proportional random sampling, with a total of 137 respondents participating in the study. The measurement tools utilized encompass scales to assess life's meaning, gratitude, and family support. The analytical approach used is multiple regression, with the assistance of SPSS 26.0 for Windows software. Research findings indicate a positive and significant relationship between gratitude and family support with the level of life's meaning among students completing their thesis in the Faculty of Ushuluddin and Religious Studies, Raden Intan Lampung State Islamic University. Therefore, the higher the level of gratitude and family support, the higher the perceived level of life's meaning for students completing their thesis.